Ruang Kelas Menuju Metaverse: Peluang dan Tantangan Transformasi Pembelajaran di Pendidikan Dasar - Wardani Siregar, Sina; Purwanti, Devi; Rizki Maulida, Laely; Yusuf Khairunnisa, Kharisma; Rizki Aji Putra, Gilang (BULETIN ADALAH, 2025)
The transformation of 21st-century education demands a shift in classrooms from transmissive learning to student-centered learning oriented toward meaningful learning experiences, particularly in elementary education. In line with the Independent Curriculum (Kurikulum Merdeka), digital technology including the metaverse is viewed as a strategic tool for enriching the learning process. This essay critically examines the transformation of classrooms toward the metaverse, highlighting its opportunities, challenges, and implementation strategies. The study's approach is conceptual and analytical, drawing on theories of social constructivism, experiential learning, and child cognitive development. The study's findings indicate that the metaverse has the potential to increase learning engagement and support concrete, differentiated, and project-based learning. However, its implementation faces challenges related to technology access, teacher readiness, pedagogical design, and ethical issues. Therefore, the use of the metaverse needs to be gradual, contextual, and aligned with the principles of the Independent Curriculum. Keywords: Classroom Transformation; Immersion Technology; Metaverse; Independent Curriculum; and Elementary Education.